Airway Inflammation and the Pathogenesis of Asthma - Paul M O'Byrne (Canadian Respiratory Journal)
Airway inflammation has been recognized for more than l00 years to be present in the airways of patients with severe asthma. Much more recently, airway intlammation has been identified to be central to the pathogenesis of all asthma. The inflammation is of a characteristic type, with the presence of activated eosinophils, mast cells and lymphocytes in bronchoalveolar lavage fluid and airway biopsies from patients with even mild asthma. Stimuli that are known to worsen asthma, such as inhaled allergens, also increase the numbers of mast cells and cosinophils in asthmatic airways. In addition, treatment with inhaled corticoteroids - the most effective treatment for asthma - improves symptoms and reduces the numbers of eosinophil s, mast cells and lymphocytes in the airways. The precise functions of the cells in promoting inflammation and causing asthma symptoms has not yet been fully elucidated. However, it is very likely that eicosanoids, such as the cysteinyl leukotrienes, are produced by eosinophils and mast cells and are a major cause of bronchoconstriction in asthma. Also, these inflammatory cells can produce proinflammatory cytokines, such as granulocytc-macrophage colony-stimulating factor. interleukin (IL) 3 and IL-5, which may promote continuing inflammation in the airways. Lastly, the persisting inflammatory cell infiltrate and products re leased from these cells arc very likely the cause or the airway structural changes characteristic of asthma, such as epithelial damage, goblet cell hyperplasia. smooth muscle thickening and deposition of collagen below the basement membrane. These changes have been suggested tn he the cause of airway hyperresponsiveness in asthma. An improved understanding of the precise mechanisms by which airway inflammation is initiated, propagates and causes airway damage will hopefully allow more precise treatment strategies to he developed for asthma than currently exist.